ANALISIS FAKTOR YANG MEMPENGARUHI PERMINTAAN RUJUKAN PASIEN BPJS KESEHATAN DI PUSKESMAS NGKERAN KECAMATAN LAWE ALAS KABUPATEN ACEH TENGGARA TIMUR TAHUN 2019 - Sinaga, Jon; Sitio, Sri Sudewi (Jurnal Inovasi Kesehatan Masyarakat, 2020)
Health services received by BPJS participants are carried out through a tiered referral mechanism, which is a definition of a health service referral system that regulates the delegation of duties and responsibilities of health services both vertically and horizontally. The purpose of this study was "To analyze the factors that influence the referral request of BPJS patients at the Puskesmas. This type of research is an explanatory research cross-sectional design with a sample of 79 BPJS patients. The results showed that there was an effect of age (p = 0.01; p <0.05), the influence of BPJS information (p = 0.01; p <0.05) on referral requests for BPJS patients with successive RP 2.17 (95% CI = 1.04-6.60) and 3.70 (95% CI = 1.27-10.7. While education, income, perceptions of illness, perceptions of officers, perceptions of service there is no influence on requests for BPJS patient referrals ( P> 0.05) The BPJS information variable in this study was the most dominant variable affecting referral requests for BPJS patients (RP = 3.70) .The results of the study concluded that there was an influence of age and BPJS information on BPJS patient referral requests. BPJS Kesehatan to pay more attention to accurate and accurate information related to the development of the health care system, both with FKTP partners and JKN participants